2005
DOI: 10.1158/0008-5472.can-04-3494
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Induced by Doxorubicin Is Deficient in Phosphorylation and Acetylation and Represses Nuclear Factor-κB–Dependent Transcription in Cancer Cells

Abstract: The primary goal of chemotherapy is to cause cancer cell death. However, a side effect of many commonly used chemotherapeutic drugs is the activation of nuclear factor-KB (NF-KB), a potent inducer of antiapoptotic genes, which may blunt the therapeutic efficacy of these compounds. We have assessed the effect of doxorubicin, an anthracycline in widespread clinical use, on NF-KB activation and expression of antiapoptotic genes in breast cancer cells. We show that doxorubicin treatment activates NF-KB signaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 26 publications
8
80
1
Order By: Relevance
“…Accordingly, NF-kB induced by doxorubicin was found to bind endogenous loci and to assemble a histone deacetylase-dependent transcriptional repressor complex (Campbell et al, 2004). Alternatively, repression may result from unstable binding of NF-kB to endogenous loci owing to deficiency of p65 in phosphorylation and acetylation (Ho et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, NF-kB induced by doxorubicin was found to bind endogenous loci and to assemble a histone deacetylase-dependent transcriptional repressor complex (Campbell et al, 2004). Alternatively, repression may result from unstable binding of NF-kB to endogenous loci owing to deficiency of p65 in phosphorylation and acetylation (Ho et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it was found that daunorubicin induced the association of RelA with the histone deacetylases 1, 2 and 3, consistent with the role for NF-kB in repressing gene expression downstream of responses to that chemotherapy. A similar report indicated that doxorubicin-induced NF-kB is deficient in transcriptional activity, which is associated with reduced phosphorylation and acetylation of RelA (Ho et al, 2005). In addition, NF-kB activation by doxorubicin in four colorectal cancer cells is required for the anticancer efficacy of the drug (Ashikawa et al, 2004).…”
Section: Nf-jb Activation and Cancer Therapymentioning
confidence: 87%
“…Indeed, doxorubicin has been shown to repress some NF-kB-driven genes by assembling a histone deacetylase-dependent transcriptional repressor complex (Campbell et al, 2004(Campbell et al, , 2006. It has also been observed that doxorubicin leads to a deficiency in phosphorylation and acetylation of p65, resulting in unstable binding of NF-kB to endogenous loci (Ho et al, 2005). The loss of p53 accentuates the decrease in isoform 3 mRNA levels, indicating that both p53 and (at least) another transcription factor, maybe NF-kB, control PIDD expression.…”
Section: Discussionmentioning
confidence: 99%